Ulnar nerve decompression with osteocapsular arthroplasty for primary elbow osteoarthritis - Hyojune Kim; Erica Kholinne; Jae-Man Kwak (Journal of Orthopaedic Surgery, 2022)
Purpose The aim of this study was to suggest treatment guidline for primary elbow OA with ulnar nerve neuropathy or high-grade stiffness by evaluating the effect of ulnar nerve decompression on the outcome of osteocapsular arthroplasty. Methods A total of 30 patients who underwent primary osteocapsular arthroplasty for elbow OA were retrospectively reviewed. The surgical outcomes were evaluated for pain score (visual analog scale; VAS), range of motion (ROM), and Mayo Elbow Performance Score (MEPS). The ulnar nerve decompression was performed for (1) ulnar nerve neuropathy, and (2) high-grade stiffness of flexion, defined as the flexion angle, is <90°. Patients were categorized into the two groups: ulnar nerve decompression group (UD group, n = 11) and the non-decompression group (Non-UD group, n = 19). The surgical outcome was compared between the groups. Results Primary elbow OA with cubital tunnel syndrome or high-grade stiffness showed comparable improvement in MEPS, VAS, and ROM arc at final follow-up in the UD group compared with the non-UD group (UD group vs. non-UD group: MEPS 85.91 vs 86.84, p -value = 0.824, VAS 1.46 vs 1.16, p -value = 0.588, ROM arc 108 vs 109, p -value = 0.949). Improvement in ROM arc at 2 years follow-up was significantly higher in UD group (UD group vs. non-UD group: ROM arc difference, 42 vs 14, p = 0.002). Conclusion Osteocapsular arthroplasty with ulnar nerve decompression for primary elbow OA with ulnar nerve neuropathy or high-grade stiffness provided improved motion arc and compatible clinical results. Level of evidence Level III, Retrospective comparative study